INCOME DISTRIBUTION OF RED CHILLI FARMER, AT MEREMBU VILLAGE, LABUAPI DISTRICT, WEST LOMBOK REGENCY 2021 - Ida Bagus Eka Artika (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
Red chili is an agricultural commodity planted by farmers on the sidelines of rice planting as the main agricultural commodity, especially in Merembu Village, Labuapi District, West Lombok Regency. This study aims to determine the level of income distribution of chili farmers in Merembu Village, Labuapi District, West Lombok Regency. The sample respondent as many as 35 red chili farmers in the research area. The analysis technique uses income distribution analysis with three approaches, namely Gini Coefficient approach, Lorenz Curve and World Bank Criteria Approach. The results of the Gini Ratio calculation for the 35 respondents studied, obtained a Gini Index or Gini Coefficient of 0.143, this shows the income inequality of red chili farmers in Merembu Village, Labuapi District in the mild or low category. This statement is reinforced by the Lorenz Curve approach and the World Bank Criteria Approach, namely the results of calculations based on the World Bank approach obtained that 40% of the population with low incomes receive an income of 29.6% or greater than 17% (Low Category) of the total existing income. This indicates that the category of the level of income distribution of chili farmers in Merembu Village, Labuapi District is relatively low